Laboratory surveillance of influenza virus in children under 10 years old, in northern Greece, during 2004-2010 - Gioula, G (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2013)
Objectives: Influenza viruses constitute one of the most common pathogens that cause acute respiratory disease in children. The aim of this study is to present the contribution of influenza viruses to influenza-like illness (ILI) in children (aged<10 years old) in Northern Greece during six influenza seasons (2004-2010). Materials and Methods: 1,242 pharyngeal swabs or/and washes from children younger than 10 years old, presented as ILI infections during the last six influenza seasons (2004-2005, 2005-2006, 2006-2007, 2007-2008, 2008-2009 and 2009-2010) were examined for influenza A and B by Real-time one step RT-PCR. Results: Influenza viruses were detected in 431 (34.7%) of the 1,242 specimens. In a total of 372 specimens were positive for influenza A and 58 for influenza B. The majority of the infected young patients were 6-10 years old (51.9%). Conclusion: Our results show that in N. Greece, influenza viruses type A and B contribute to ILI presenting infections at a rate of 34.7 % in children younger than 10 years old.